1984
DOI: 10.1007/bf00433392
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physiological responses of normotensive and essentially hypertensive men to exercise in the heat

Abstract: Six essentially hypertensive men (average resting arterial pressure of 150/97 mm Hg) and eight normotensive controls (average resting arterial pressure of 115/73 mm Hg) were tested during 1 h of dynamic leg exercise in a warm environment. The groups were well matched for age, VO2 max, body surface area, weight, and body fat. Environmental conditions were 38 degrees C dry-bulb, 28 degrees C wet-bulb; exercise intensity was approximately 40% VO2 max (85-90 W). There were no significant intergroup differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
3
35
1
Order By: Relevance
“…cannot be compared to the whole-body observations reported in the present study. Importantly, we show that physiologically-relevant reductions in SkBF, such as those that occur with ageing (Kenney et al , 1997; Minson et al , 1998), and disease (Kenney & Kamon, 1984; Green et al , 2006), are unlikely to affect whole-body heat loss potential.…”
Section: Discussionmentioning
confidence: 79%
“…cannot be compared to the whole-body observations reported in the present study. Importantly, we show that physiologically-relevant reductions in SkBF, such as those that occur with ageing (Kenney et al , 1997; Minson et al , 1998), and disease (Kenney & Kamon, 1984; Green et al , 2006), are unlikely to affect whole-body heat loss potential.…”
Section: Discussionmentioning
confidence: 79%
“…58,59 Meanwhile, Carberry et al 60 found that resting maximal forearm SkBF response to local heating (44°C) was reduced in hypertensive individuals compared with age-and weight-matched normotensive controls. Similarly, during moderate-intensity exercise (40% VO 2max ) in the heat (38°C), Kenney et al 61,62 found attenuated increases in forearm blood flow in hypertensive participants compared with normotensive controls. The authors surmised that structural alterations in the vasculature (thickened media and/or an increase in smooth muscle layers) would diminish vasodilation in response to increased thermal stimuli.…”
Section: Hypertensionmentioning
confidence: 97%
“…During exerciseinduced heat stress, people with hypertension experience an elevated blood pressure response and possibly greater thermal strain than people with normotension. 44 In earlier studies, Kenney and collaborators 44,45 found that the increases in forearm blood flow during exercise-induced hyperthermia, which are primarily confined to the skin, 46 were markedly reduced in people with hypertension relative to people with normotension. This effect could result in a reduction in heat transfer from the body core to the skin, which would increase the potential for heat illness.…”
Section: Hypertensionmentioning
confidence: 99%